Tumor Delivery of Chemotherapy Combined with Inhibitors of Angiogenesis and Vascular Targeting Agents - Cesca, Marta; Bizzaro, Francesca; Zucchetti, Massimo; Giavazzi, Raffaella (Frontiers in Oncology, 2013)
Numerous angiogenesis-vascular targeting agents have been admitted to the ranks of cancer therapeutics; most are used in polytherapy regimens. This review looks at recent progress and our own preclinical experience in combining angiogenesis inhibitors, mainly acting on VEGF/VEGFR pathways, and vascular targeting agents with conventional chemotherapy, discussing the factors that determine the outcome of these treatments. Molecular and morphological modifications of the tumor microenvironment associated with drug distribution and activity are reviewed. Modalities to improve drug delivery and strategies for optimizing combination therapy are examined.